Mind Mapping Learning Media on the ADDIE Model Class VIII Prayer Pillar Material of SMPDT Bandung - Safwandy Nugraha, Mulyawan; Furqon, Zenal; Dedih, Ujang (Zona Education Indonesia, 2024)
This research was taken from curiosity regarding learning media in the ADDIE model which can foster student creativity, namely mind mapping media. This research aims to find out how the development of mind mapping learning media using the ADDIE model can increase student creativity in the pillars of prayer material. The method used in this research is the research and development method, where this research aims to produce a media tool, material or learning strategy. This research method uses the ADDIE research model (Analyze, Design, Development, Implementation and Evaluation). The ADDIE model chosen by the author is because it is in accordance with the development of Mind Mapping media which consists of 5 implementation stages in research. The mind mapping learning media developed in this research received a score of 3.5 (very valid) which has been validated by one expert validator. Obtaining these scores can be concluded that the mind mapping media that has been developed in this research is very valid for learning material on the pillars of prayer in class VIII PAI learning